2021
DOI: 10.1002/art.41697
|View full text |Cite
|
Sign up to set email alerts
|

A Proinflammatory Cytokine Network Profile in Th1/Type 1 Effector B Cells Delineates a Common Group of Patients in Four Systemic Autoimmune Diseases

Abstract: Objective. The effector T cell and B cell cytokine networks have been implicated in the pathogenesis of systemic autoimmune diseases, but the association of these cytokine networks with the heterogeneity of clinical manifestations and immune profiles has not been carefully examined. This study was undertaken to examine whether cytokine profiles can delineate distinct groups of patients in 4 systemic autoimmune diseases (systemic lupus erythematosus, Sjögren's syndrome, rheumatoid arthritis, and systemic sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…This study conducted in Poland would need to be generalized to more patients, but it reinforces the fact that a holistic approach to RA treatment, with multiple cytokine targets, could be highly beneficial for patients. These results are in line with the fact that both IL-2 and TNF-α were found to be parts of a specific pro-inflammatory cytokine profile also defined by high levels of CXCL10 and IL-6, characterizing severe outcomes in systemic autoimmune diseases [100].…”
Section: Micro-immunotherapy: a Multiple Immune-targeted Ultra-low-dose-based Strategy To Calm Chronic Inflammation In Rasupporting
confidence: 85%
“…This study conducted in Poland would need to be generalized to more patients, but it reinforces the fact that a holistic approach to RA treatment, with multiple cytokine targets, could be highly beneficial for patients. These results are in line with the fact that both IL-2 and TNF-α were found to be parts of a specific pro-inflammatory cytokine profile also defined by high levels of CXCL10 and IL-6, characterizing severe outcomes in systemic autoimmune diseases [100].…”
Section: Micro-immunotherapy: a Multiple Immune-targeted Ultra-low-dose-based Strategy To Calm Chronic Inflammation In Rasupporting
confidence: 85%
“…The in-vitro -induced Be1 and Be2/Breg were obtained in coculture with naive and memory T cells, respectively, as previously described ( 126 ). After coculture, B cells were sorted with the “FACS MoFlo XDP cell sorter” (Beckman Coulter) with a purity greater than 98%.…”
Section: Methodsmentioning
confidence: 99%
“…We recently developed an in vitro model of B-cell polarization to induce pro-inflammatory B (Be1) cells and Bregs suppressing CD4 + T cell proliferation ( 126 ). In vitro- induced Breg cells included mostly activated B cells (IgM + CD38 + CD27 - ) and unswitched PB (CD19 + IgM + CD27 low CD38 + CD20 + ) able to simultaneously produce IL-10 and IgM.…”
Section: C-maf As a Key Driver Of The B-cell Immunoregulatory Function?mentioning
confidence: 99%
“…Patients were found to primarily have increases in CXCL10, IL-2, IL-6, and tumor necrosis factor (TNF). The pro-inflammatory profile was also characterized by an abnormal B cell distribution, a CD8 cytotoxic T cell signature, and more severe clinical features ( 76 ). In vitro study suggested upregulation of this cytokine signature associated with B cell enhancement of Th1 differentiation and proliferation of activated naive T cells ( 76 ).…”
Section: Cytokinesmentioning
confidence: 99%